Expression of miR200a as a biomarker in women with preterm delivery - Effat Seyed Hashemi; Roghaye Dargahi; Malihe Entezari; Seyed Saeed l Hosseini As (Mashhad University of Medical Sciences, 2019)
Introduction: Preterm delivery is one of the main health problems and after congenital anomalies is the main cause of neonatal disease and mortality. Considering the main role of microRNAs as Biomarkers in the diagnosis of various types of diseases, this study was performed with aim to investigate the expression of miR200a as a biomarker in women with preterm delivery in Ardabil province. Methods: This case-control study was performed on 50 healthy nulliparous women and 50 nulliparous women who had referred to Ardabil Alavi hospital for preterm labor from October 2017 to December 2018. After extracting MicroRNA and synthesis of cDNA, real time PCR technique was used to determine miR200a expression. Data were analyzed by SPSS software (version 20) and ANOVA, t-test, and v-one test. P<0.05 was considered statistically significant. Results: The expression of miR200a in the normal group was 0.35±0.04, and in the preterm delivery group was 0.24± 0.09 that had 11% decreases in expression compared to the healthy group. Also, specificity and sensitivity of this test for evaluation of preterm delivery was 53.4% and 74%, respectively, which was assessed by ROC curve. These results were statistically significant (P ≤ 0.05). Conclusion: The expression of microRNA200a as a Biomarker was different among normal pregnant women and those with preterm delivery; it seems that microRNA200a can be used as a new marker to predict preterm delivery.